Organized crime and the challenge to democracy - Allum, Felia, 1971-; Siebert, Renate, 1942- (Routledge/ECPR studies in European political science ;, 2003)
This innovative book investigates the paradoxical situation whereby organized crime groups, authoritarian in nature and anti-democratic in practice, perform at their best in democratic countries.